Evaluation of waste sorting and recycling laboratory in Mahmudiya (case study) - سلوم تاميم محمد; نور خليل ابراهيم (Journal of Economics and Administrative Sciences, 2019)
The daily practices of humans produce various types of waste, which are a threat to the health and environment surrounding it, especially after the increase in quantities as a result of population growth and technological development, and here came the need for recycling solid waste as one of the modern concepts that achieve environmental benefits, The aim of the research is to evaluate the project of sorting and recycling of solid waste in the district of Mahmoudiya and whether its work is sustainable ,Conforming to modern standards, using standard checklists to determine the gap between the current laboratory reality and the requirements of those standards , Using the case study methodology as the most appropriate approaches to the problem of research, and was reached several conclusions, including the most important sorting and recycling plant is not sustainable and did not achieve material profits during the research period.